The Effect Of Work Supervision, Organizational Commitment, And Job Satisfaction On Employee Performance At Pt Bank Rakyat Indonesia (Persero) Tbk Iskandar Muda Medan Branch - Ridha Safira; Juniarti Juniarti; Teguh Wahyono (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of work supervision, organizational commitment, and job satisfaction on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk Iskandar Muda Medan Branch. A quantitative descriptive approach was employed, utilizing SPSS version 26 for statistical analysis. The population comprised 79 permanent employees, sampled via census (non-probability saturated sampling) due to size under 100. Partial t-test results indicate significant positive effects: work supervision (t = 4.390 > 1.992), organizational commitment (t = 4.955 > 1.992), and job satisfaction (t = 2.238 > 1.992). Simultaneous F-test shows F = 69.885 > 2.73; thus, H1 accepted, H0 rejected. The coefficient of determination (R²) is 72.6%, with 27.4% explained by other unexamined variables.